Operator gender differences in major mechanical complications after central line insertions: a subgroup analysis of a prospective multicentre cohort study - Leila Naddi; Janna Hübinette; Thomas Kander; Ola Borgquist; Maria Adrian (BMC Anesthesiology, 2024)
Abstract Background A previous study on mechanical complications after central venous catheterisation demonstrated differences in complication rates between male and female operators. The objective of this subgroup analysis was to further investigate these differences. The hypothesis was that differences in distribution of predefined variables between operator genders could be identified. Methods This was a subgroup analysis of a prospective, multicentre, observational cohort study conducted between March 2019 and December 2020 including 8 586 patients ≥ 16 years receiving central venous catheters at four emergency care hospitals. The main outcome measure was major mechanical complications defined as major bleeding, severe cardiac arrhythmia, pneumothorax, arterial catheterisation, and persistent nerve injury. Independent t-test and χ2 test were used to investigate differences in distribution of major mechanical complications and predefined variables between male and female operators. Multivariable logistic regression analysis was used to determine association between operator gender and major mechanical complications. Results Female operators had a lower rate of major mechanical complications than male operators (0.4% vs 0.8%, P = .02), were less experienced (P < .001), had more patients with invasive positive pressure ventilation (P < .001), more often chose the internal jugular vein (P < .001) and more frequently used ultrasound guidance (P < .001). Male operators more often chose the subclavian vein (P < .001) and inserted more catheters with bore size ≥ 9 Fr (P < .001). Multivariable logistic regression analysis showed that male operator gender was associated with major mechanical complication (OR 2.67 [95% CI: 1.26–5.64]) after correction for other relevant independent variables. Conclusions The hypothesis was confirmed as differences in distribution of predefined variables between operator genders were found. Despite being less experienced, female operators had a lower rate of major mechanical complications. Furthermore, male operator gender was independently associated with a higher risk of major mechanical complications. Future studies are needed to further investigate differences in risk behaviour between male and female operators. Trial registration Clinicaltrials.gov identifier: NCT03782324. Date of registration: 20/12/2018.